Transforming Environmental Water Management to Adapt to a Changing Climate - Capon, Samantha J.; Leigh, Catherine; Hadwen, Wade L.; George, Amy; McMahon, Joe M.; Linke, Simon; Reis, Vanessa; Gould, Leigh; Arthington, Angela H. (Frontiers in Environmental Science, 2018)
Environmental water management has become a global imperative in response to environmental degradation and the growing recognition that human well-being and livelihoods are critically dependent on freshwater ecosystems and the ecological functions and services they provide. Although a wide range of techniques and strategies for planning and implementing environmental flows has developed, many remain based on assumptions of hydrologic stationarity, typically focusing on restoring freshwater ecosystems to pre-development or ‘natural’ conditions. Climate change raises major challenges to this conventional approach, in part because of increasing uncertainties in patterns of water supply and demand. In such a rapidly changing world, the implementation of, and capacity of water managers to deliver flow regimes resembling historical hydrological patterns may be both unfeasible and undesirable. Additionally, as emphasis shifts from species-focused water allocation plans towards a greater appreciation of freshwater ecological functions and services, many of which will be influenced by climate change, a thorough re-evaluation of the conventional objectives, planning, delivery and monitoring of environmental water, including its role in the broader context of water and environmental management, is essential. Here, we identify the major challenges posed by climate change to environmental water management and discuss key adaptations and research needed to meet these challenges to achieve environmental and societal benefits and avoid maladaptation.